Ukuran Perusahaan, Struktur Modal, Dan Nilai Perusahaan : Profitabilitas Sebagai Variabel Intervening (Studi Empirik pada Perusahaan Sub Sektor Perkebunan) - Arifian Ade Fitra; Ika Utami Widyaningsih (Universitas Sultan Ageng Tirtayasa, 2022)
The plantation sub-sector tends to have a large company size and a capital structure consisting mostly of debt. The purpose of this study was to determine whether company (firm) size and capital structure can affect firm value with profitability as the intervening variable. The samples used were 14 companies in the plantation sub-sector. The results show that firm size has a significant negative effect on firm value; capital structure has no effect on firm value; and path analysis prove that profitability is not able to mediate the effect of firm size on firm value, nor is it able to mediate the effect of capital structure on firm value.